(untitled) (Publicaciones en Ciencias y Tecnología, 2013)
Service sector has become the most important aspect in advanced economies, in terms of production volume such as employment, with a significant increase since the 70s worldwide. In service organizations, unlike the manufacturing sector, efectively in organization depends on productivity and quality which are seen as inseparable phenomena. In this exploratory paper, we made an analysis on research productivity and quality in services based on various authors, in order to show the relationship between productivity and quality in the services sector SMEs, and how the characteristics of SMEs become more important the relationship between the two. As a result identifies five aspects that relate quality and productivity in Services Sector SMEs expressed in use of external and internal indicators for measuring, effect of variations in inputs controlled by the organization, impact of interactions between customer and service provider and mutual understanding developed in these interactions, the importance of customer involvement as co-producer of service, and relevance of intangibles in evaluating the same.